( x + 1 ) ( x + 2 ) ( x + 3 ) = ( x + 4 ) ( x + 5 ) ( x + 6 ) 7 2 0
Find sum of all real solutions of the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Exact same procedure! Nice solution :) Btw, you made a typo in the second line
( x + 1 ) ( x + 6 ) × ( x + 2 ) ( x + 5 ) × ( x + 3 ) ( x + 4 ) = 7 2 0
Problem Loading...
Note Loading...
Set Loading...
( x + 1 ) ( x + 2 ) ( x + 3 ) ( x + 4 ) ( x + 5 ) ( x + 6 ) = 7 2 0
Now start grouping ( x + 1 ) ( x + 6 ) × ( x + 2 ) ( x + 5 ) × ( x + 3 ) ( x + 4 ) = 7 2 0 ( x 2 + 7 x + 6 ) ( ( x 2 + 7 x + 1 0 ) ) ( x 2 + 7 x + 1 2 ) = 7 2 0
Assume x 2 + 7 x = p
Now equation becomes ( p + 6 ) ( p + 1 0 ) ( p + 1 2 ) = 7 2 0 p 3 + 2 8 p 2 + 2 5 2 p + 7 2 0 = 7 2 0 p ( p 2 + 2 8 p + 2 5 2 ) = 0
So, one solution is p = 0 ⟹ x 2 + 7 x = 0 ⟹ x = 0 , − 7
Next quadratic part has negative discriminant so there exists no real solution.
Sum of real roots 0 + ( − 7 ) = − 7